2006
DOI: 10.1080/08039480500504933
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosed and self-reported childhood abuse in national and regional samples of child and adolescent psychiatric patients: Prevalences and correlates

Abstract: We investigated if rates of ICD-10 axis 5 abuse diagnoses in the total child psychiatric population in Norway were different from self-reported abuse at 12-18?years of age, and we investigated their respective correlates. Study 1: The official registers of the total child psychiatric population in Norway in the years 2000 and 2001 were analysed for rates and correlates of axis 5 diagnoses of sexual and physical abuse. Study 2: Self-reports of abuse and neglect in a representative clinical sample of 129 adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 43 publications
1
25
0
3
Order By: Relevance
“…A number of studies document a discrepancy between offi cial numbers and data from epidemiological research [45][46][47]. Shaff er et al argue that diff erences in study designs (prospective, retrospective or combined designs) are responsible for broad ranges [5].…”
Section: Summary Of Results and Conclusionmentioning
confidence: 99%
“…A number of studies document a discrepancy between offi cial numbers and data from epidemiological research [45][46][47]. Shaff er et al argue that diff erences in study designs (prospective, retrospective or combined designs) are responsible for broad ranges [5].…”
Section: Summary Of Results and Conclusionmentioning
confidence: 99%
“…This is also true for childhood adversities [27,28]. In particular, it has been suggested that the development of cannabis abuse and dependence symptoms are influenced by childhood maltreatment both directly and through the development of externalizing (but not internalizing) disorders [29].…”
Section: Introductionmentioning
confidence: 93%
“…Additionally, using a list of examples, participants were asked whether they had experienced emotional, psychological, physical and/or sexual abuse [27,41,42]. The examples included parental ignorance of one's problems and experiences, being subordinated to siblings, being beaten up or being touched or having to touch someone in a sexual way.…”
Section: Childhood Adversitiesmentioning
confidence: 99%
“…I McFarlanes undersøkelse fra 2006 som er referert over var det hele 56% av de som hadde opplevd vold og seksuelle overgrep der dette ikke var nevnt i pasientenes journaler. I en norsk undersø-kelse (Reigstad et al 2006), var det 60,2% av 129 ungdommer som gikk i behandling i Barne-og ungdomspsykiatriske poliklinikker som på en spørreundersøkelse rapporterte å ha vaert utsatt for fysisk mishandling eller seksuelt misbruk. Imidlertid var det kun 1,6-1,9% (i og utenfor familie) av de samme 129 ungdommene som hadde fått diagnostisert seksuelt misbruk, og kun 0,4% av ungdommene som hadde fått diagnostisert at de hadde vaert utsatt for vold.…”
Section: Vedleggunclassified